Education, Religious Authority and Moderation: Muslim Scholars-Cum-Leaders in Brunei Darussalam - Haji Mail, Haji Awg Asbol bin; Mansurnoor, Iik Arifin (ASPENSI in Bandung, Indonesia, 2009)
ABSTRACT: Brunei Darussalam is known to be one of the countries in contemporary Southeast Asia which has not experienced the birth of modern radical Muslims or Islamic organizations on its own soil. Obviously, the political system and state structure have a lot to do with such a condition; however, from the purely socio-religious perspective it is certainly interesting to examine the educational and religious backgrounds of the countrys Muslim leaders and scholars or âulamaâ. This paper addresses the structural link between state and education, especially religious education, and its impact on the kind of education, training and career Bruneis âulamaâ have. Bruneis prominent âulamaâ went through particular educational centers and underwent certain training. However, they also had diverse interests and extra-activities which eventually formed their personal stature and religious characteristics. By identifying the many facets of their intellectual passages and training, this paper sheds some light on how the scholar-cum-leaders fit to the state structure and maintain religious stability in the country.KEY WORDS: state of Brunei, religious education, impact on society, the scholar-cum-leaders, and religious stability in the country.Â Â About the Authors: Assoc. Prof. Dr. Haji Awg Asbol bin Haji Mail and Prof. Dr. Iik Arifin Mansurnoor are Lecturers at the History Department, Faculty of Art and Social Sciences UBD (University of Brunei Darussalam). They can be reached at: asbolm@hotmail.com and iik@yahoo.comHow to cite this article? Haji Mail, Haji Awg Asbol bin & Iik Arifin Mansurnoor. (2009). âEducation, Religious Authority and Moderation: Muslim Scholars-Cum-Leaders in Brunei Darussalamâ in TAWARIKH: International Journal for Historical Studies, Vol.1(1) October, pp.15-56. Bandung, Indonesia: ASPENSI [Asosiasi Sarjana Pendidikan Sejarah Indonesia], ISSN 2085-0980. Chronicle of the article: Accepted (August 17, 2009); Revised (September 20, 2009); and Published (October 28, 2009).